2020
DOI: 10.1007/s00535-020-01701-y
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-based diagnostic approach for eosinophilic esophagitis

Abstract: The prevalence of eosinophilic esophagitis (EoE) has been increasing in Japan. Although the diagnosis of EoE is based on simple criteria that include the presence of esophageal symptoms and esophageal eosinophilia on biopsies, there are several important issues associated with the diagnostic approach. Following an extensive literature search, the symptoms of 886 EoE cases in Japanese adults were analyzed and divided into three categories as follows: (1) typical symptoms, such as dysphagia (53%); (2) other uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…A younger age and diffuse disease distribution at the first detection in endoscopic findings are considered to be risk factors for progression to symptomatic EE in aEE patients ( 10 , 20 ). Recent review articles have suggested the utility of a symptom-based diagnostic and therapeutic approach for EoEs ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A younger age and diffuse disease distribution at the first detection in endoscopic findings are considered to be risk factors for progression to symptomatic EE in aEE patients ( 10 , 20 ). Recent review articles have suggested the utility of a symptom-based diagnostic and therapeutic approach for EoEs ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 Fujiwara analyzed symptoms in 886 EoE cases in Japanese adults and divided the symptoms into the following three categories: (i) typical symptoms, such as dysphagia (53%); (ii) other upper GI symptoms (40%); and (iii) no symptoms found during screening or medical examinations, i.e., "asymptomatic esophageal eosinophilia" (19%). 29 Questions arise as to whether the pathology of EoE would be different depending on the presence or absence of symptoms and whether it could be possible to objectively evaluate subjective symptoms. Muroi et al, who won the Young Investigator Award at the 98th symposium, conducted a unique study using endoscopic ultrasonography (EUS) and high-resolution manometry (HRM) to examine the difference in pathological conditions between symptomatic and asymptomatic EoE.…”
Section: Eosinophilic Esophagitis Functional Evaluationmentioning
confidence: 99%
“…34 The natural history of Japanese EoE, especially asymptomatic EoE, has not yet been completely elucidated. 29…”
Section: Asymptomatic Eoementioning
confidence: 99%
“…Moreover, the prevalence of esophageal eosinophilia on biopsy in cases with typical endoscopic EoE findings was low (11.1-30.8%) in three previous studies. 13 Therefore, multiple biopsies of esophageal mucosa in cases suspicious of EoE are proposed and are the only modality that can exclude EoE when no significant esophageal eosinophilia is observed.…”
Section: Endoluminal Treatmentsmentioning
confidence: 99%